Refocusing Sustainability Education: Using Students’ Reflections on Their Carbon Footprint to Reinforce the Importance of Considering CO2 Production in the Construction Industry - Weirs, John; Osborne, Allan (Frontiers in Built Environment, 2020)
The construction industry is the most significant contributor to the UK’s CO2 emissions. It is responsible for an annual output of approximately 45% of the total. This figure highlights the role the industry must play in helping to achieve the UK Government’s CO2 reduction target. It is ergo incumbent on construction-related educators to emphasise this issue and explore ways in which it can be achieved. Unintentional desensitisation has resulted in the term ‘sustainability’, particularly CO2 production, being seen by students as just another concept to be studied from a theoretical perspective. Many students fail to grasp its broader implications and how it should affect strategic environmental decisions about construction processes, technologies, and products. In an attempt to address this problem, an innovative learning, teaching, and assessment strategy was used with final year undergraduate construction students to improve their level of sustainability literacy. The theory of threshold concepts in the context of transformative learning was used as the baseline philosophy to the study. The approach involved asking students to calculate their carbon footprint and to reflect upon and extrapolate their findings to the construction industry and its practice. Content analysis was performed on the reflective commentaries acquired from student portfolios collected over four academic years. The results showed how the students’ reflections on their carbon footprints proved to be an enlightening experience. Terms such as ‘shocked by my footprint’, ‘surprised at the findings’, and ‘change in attitude’ were among the contemplative comments. When students linked their findings to the construction industry, phrases such as ‘waste generation’, ‘technologies’, and ‘materials’ were some of the concepts considered. By using their personal experiences as a benchmark, students were able to gain a deeper level of understanding of the causes and consequences of CO2 production. They also found it more straightforward to relate these issues to the construction industry and its practice. Several novel recommendations are made to raise the level of sustainability literacy in the construction industry thereby facilitating a potential reduction in worldwide CO2 production.